2012
DOI: 10.1176/appi.ajp.2012.12010087
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Comorbidity Between Attention Deficit Hyperactivity Disorder and Bipolar I Disorder: A Meta-Analysis of Family Genetic Studies

Abstract: The results suggest that ADHD plus bipolar comorbidity cannot be accounted for by misdiagnoses, but additional research is needed to rule out artifactual sources of comorbidity. More research is also needed to determine whether comorbidity of ADHD and bipolar I disorder constitutes a familial subtype distinct from its constituent disorders, which if confirmed would have implications for diagnostic nosology and genetic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 73 publications
3
50
1
1
Order By: Relevance
“…Consistent with that report, the polygenic risk score derived from a large GWAS of schizophrenia significantly discriminated ADHD cases from controls [108]. This discrimination was strongest for alleles that were risk alleles for both adult schizophrenia and adult bipolar disorder, which confirms prior family and twin data suggesting a genetic link between ADHD and bipolar disorder [109]. Moreover, a joint GWAS of ADHD and bipolar disorder reported a significant correlation between the polygenic scores of ADHD and bipolar disorder and also identified genome-wide significant loci for the two disorders [110].…”
Section: Common Variant Adhd As a Polygenic Disordersupporting
confidence: 85%
“…Consistent with that report, the polygenic risk score derived from a large GWAS of schizophrenia significantly discriminated ADHD cases from controls [108]. This discrimination was strongest for alleles that were risk alleles for both adult schizophrenia and adult bipolar disorder, which confirms prior family and twin data suggesting a genetic link between ADHD and bipolar disorder [109]. Moreover, a joint GWAS of ADHD and bipolar disorder reported a significant correlation between the polygenic scores of ADHD and bipolar disorder and also identified genome-wide significant loci for the two disorders [110].…”
Section: Common Variant Adhd As a Polygenic Disordersupporting
confidence: 85%
“…This same study found a 26.2% 12-month occurrence of any mental health condition, a 14.4% 12-month occurrence of one mental health condition, a 5.8% 12-month occurrence of two mental health conditions, and a 6% 12-month occurrence of three or more mental health conditions (Kessler et al 2005). A large body of research indicates that the five conditions investigated in this study are highly comorbid with each other as well as with additional diagnoses (Alegría et al 2010;Bernardi et al 2012;Biederman et al 1995;Brawman-Mintzer et al 1993;de Graaf et al 2002;Faraone et al 2012;Kessler et al 2006;McElroy et al 2001;McGough et al 2005;Sachs et al 2000;Simon et al 2004).…”
Section: Addictionmentioning
confidence: 98%
“…ADHD increased the risks of attempted and completed suicide, even after adjusting for comorbid psychiatric disorders (odds ratio (OR)=3. 62 …”
Section: Mood Suicidality and Psychosismentioning
confidence: 99%